Nursing work in Spain and Cuba: an exchange experience. - María de los Angeles Villegas Dorticós; Dinorah Herrera Cañellas; Vicia Dora Jiménez; Lidia Cabrera Torralba; Héctor Cabrera Rodríguez (Medisur)
A descriptive study was performed in 5 students from Granada that were in their working practices in Cienfuegos; mainly in policlinics, maternity homes, family doctors offices etc. as part of the agreement between Granada university and Cienfuegos Medicine School. Our experience has been very positive both, in the professional and personal field. The interchange between paramedical staff of both countries developed solidarity and humanism. This exchange allows knowing the high degree of transmissible diseases due to immigrants' arrival, lack of epidemiological control and waste of material and money. We can assure that the main achievement of this experience was encounter of these visitors with other Spanish students and teachers in the University of Granada. This activity was different from the traditional university lecture.